Strategy of Tourism Development for the Middle-Sized Town: From Scenarios to Strategic Maps - LEVYTSKA, Inna; KLYMCHUK, Alena; NATALIYA, Biletska; KOTSERUBA, Nataliia (Journal of Environmental Management and Tourism, 2020)
A city that does not have a bright tourism brand needs to take special approaches to planning and implementing a tourism strategy. Such a strategy should be an integral part of the overall city development strategy, consider the interests of all stakeholders, have its own vision, scenarios, projects. An intercultural approach from "history to the present", emphasis on different target groups, active partnership with business and community are the basis for formulating an effective city development strategy. The author considers an example of strategy development for Vinnytsia using strategic, project and operational management methods and tools. The directions of analysis and development from vision to real scenarios and vice versa from scenarios to strategic map of development allow to form a real strategy of tourism development. In each direction the main functions of management are considered: planning, motivation, organization, control. The analysis of the overall strategy of the city development revealed the direct and indirect strategic projects that influence the development of tourism. W. Disney's (improved by R. Dilts) technique was used to form a vision for tourism development in the city. The main modern slogan of the development strategy of the Vinnytsia city - "City of ideas" - for tourism strategy has been transformed into the slogans "Tourist city of ideas" and "City of tourist ideas". Each of the directions of the overall city strategy is adapted to aspects of tourism development. Analysis of tourism development strategies of such cities as Zaporizhzhia, Mukachevo, Khmilnyk; a review of scientific articles on tourism strategy development has allowed us to draw on a general outline for strategy development and generate a strategic map using Google software. The analysis of the results of the activities of the the City Marketing and Tourism Department for 7 months revealed some duplications and mistakes in the formation of development goals, lack of differentiation of directions and development of partnership. The author offers rough drafts of vision, mission. In addition, recommendations were made for the City Marketing and Tourism Department. The author proposes to adapt the technology of detailing each of the directions of tourism development in the city and to position each specialist in the strategy map. The result of the research is the proposed methods and draft essays for the formation of tourism development strategy in Vinnytsia.